2016
DOI: 10.1590/0102-311x00017816
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence and early interruption of exclusive breastfeeding in the first three months of life

Abstract: The aim of this study was to investigate the role of intimate partner violence in the early interruption of exclusive breastfeeding in the first three months of life. We used data from a prospective cohort of 564 children attending four primary health clinics in Rio de Janeiro, Brazil. Interruption of exclusive breastfeeding was defined as a child receiving any kind of liquid or solid, regardless of breast milk intake, measured by a 24 hour recall. The Portuguese version of the Conflict Tactics Scales (CTS-1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 11 publications
1
13
1
Order By: Relevance
“…This is in line with previous publications that have found an association between low education, lower maternal age, and early complementary feeding [14,15,[30][31][32]. Domestic violence, particularly from an intimate partner, has been studied as a risk factor for inadequate breastfeeding practices [7][8][9][10], and such practices are related to the introduction of complementary feeding. We found that, following a multivariate analysis, exclusive breastfeeding at 90 days was a protective factor against early complementary feeding.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is in line with previous publications that have found an association between low education, lower maternal age, and early complementary feeding [14,15,[30][31][32]. Domestic violence, particularly from an intimate partner, has been studied as a risk factor for inadequate breastfeeding practices [7][8][9][10], and such practices are related to the introduction of complementary feeding. We found that, following a multivariate analysis, exclusive breastfeeding at 90 days was a protective factor against early complementary feeding.…”
Section: Discussionsupporting
confidence: 87%
“…Breastfeeding duration and practices may be influenced by many factors, including maternal age, education, stress, and depressive symptoms [7]. A number of studies have found that mothers who suffer domestic violence have lower breastfeeding intention and initiation [7], as well as earlier cessation of exclusive breastfeeding, than those who do not [7][8][9][10]. The prevalence of exclusive breastfeeding in children under 6 months is 41.6% worldwide [11].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 8 reported lower breastfeeding intention, breastfeeding initiation, and exclusive breastfeeding during the first 6 months of the child’s life, and a higher likelihood of early termination of exclusive breastfeeding, among mothers who experienced IPV. Only 6 studies were from LMICs [1318], and of these only 2 measured a mother’s exposure to emotional violence. Early initiation of breastfeeding (within 1 hour after birth) was measured in few studies [15,18].…”
Section: Introductionmentioning
confidence: 99%
“…[3] Few studies have investigated the effect of IPV on breastfeeding. Most studies are from America [14, 15, 17–20] or Asia. [13, 2123] A systematic review from 2017[24] showed that just one African study has been published.…”
Section: Introductionmentioning
confidence: 99%